Novel binary addition tree algorithm (BAT) for calculating the direct lower-bound of the highly reliable binary-state network reliability - Yeh, Wei-Chang; Tan, Shi-Yi; Zhu, Wenbo; Huang, Chia-Ling; Yang, Guang-yi (Reliability engineering & system safety, 2022)
•A new binary-addition tree algorithm (BAT) called the AppBAT is proposed.•A new lower-bound of the network reliability is proposed using the AppBAT.•AppBAT outperforms Monte Carlo Simulations (MCS) and other reliability bound algorithms.•AppBAT can overcome the obstacle of NP-hardness by finding a good solution.•AppBAT also can be improved by combining MCS-based algorithms. Real-world applications such as the internet of things, wireless sensor networks, smart grids, transportation networks, communication networks, social networks, and computer grid systems are typically modeled as network structures. Network reliability represents the success probability of a network and it is an effective and popular metric for evaluating the performance of all types of networks. Binary-state networks composed of binary-state (e.g., working or failed) components (arcs and/or nodes) are some of the most popular network structures. The scale of networks has grown dramatically in recent years. For example, social networks have more than a billion users. Additionally, the reliability of components has increased as a result of both mature and emergent technology. For highly reliable networks, it is more practical to calculate approximated reliability, rather than exact reliability, which is an NP-hard problem. Therefore, we propose a novel direct reliability lower bound based on the binary addition tree algorithm called AppBAT to calculate approximate reliability. The efficiency and effectiveness of the proposed reliability bound are analyzed based on time complexity and validated through numerical experiments.